Interactive e-learning in pharmacology to enhance student competency in faculty of medicine UII - Putrya Hawa (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2016)
Background : E-learning provides an opportunity for students to improve their knowledge by promoting self-directed learning. The aim of this e-learning is to encourage pharmacology active learning among undergraduate students in Faculty of Medicine UII. Objective : The aim of the study is to assess the effectiveness of the e-learning module in pharmacology, and the acceptability and student’s perception about the interactive e-learning module in pharmacology. Methods : This was an observational study, conducted on all medical student in Gastrointestinal module (Module 1) and Endocrine module (Module 2). Students were encouraged to register in website. By administrator approval, student can access to quiz. Another menus in the website after quiz are lectures, videos and semi-animated based CAL (computer assisted learning). Learning achievement were assessed based on module exam in pharmacology section. Feedback questionnaire were distributed to all medical student at the end of module. Results : The student’s access rate for e-learning module quiz in Module 1 is 100% and 35,48% in Module 2. In Module 1 about 75% questions have DMR value >75%. This value are increased than last year (54,5%) In Module 2, 30% questions have DMR value >75%. This value also increased than last year (0%). All students (100%) stated that e-learning in pharmacology modules are usefull. 78% stated that the website are informative and 74% admitted the material easy to access, 89,02% agreed that e-learning increase student’s motivation. Conclusion : Curriculum innovation as e-learning modules considerably was effective enhance student achivement in pharmacology. This innovation also well perceived among the student. All students agrreed that e-learning module were usefull.